Assessing the impact of the ECB's monetary policy on the stock markets: A sectoral view - Konstantin Kholodilin; Alberto Montagnoli; Oreste Napolitano; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper analyzes the response of the European stock markets to the monetary policy shocks by the European Central Bank using the heteroskedasticity based approach of Rigobon (2003). We find that monetary policy tightening has a heterogeneous impact on the Euro Area sectors on the day the monetary policy is publicly announced. Furthermore, we provide statistical evidence against the use of the popular event study approach when assessing the impact of monetary policy shocks on the stock market as the maintained assumptions can be rejected for the aggregate stock market and for most of the sectoral stock market indexes.
Keywords: E44; E47; E52; 330; Monetary policy; Stock markets; ECB; Geldpolitik; Schock; Börsenkurs; Branche; Europäische Wirtschafts- und Währungsunion; EU-Staaten